Personal Dimension in Linguostylistic Studies (to the Anniversary of Professor Svitlana Bohdan) (Linguostylistic Studies, 2021)
The article analyzes the scientific achievements of the famous linguist S.K. Bohdan and elucidates her scientific priorities and the path of their formation and development. The article provides a detailed analysis of the scholar’s scientific interests range, laying emphasis on the issues related to linguostylistics, ethnolinguistics, and linguopersonology. The studies mostly deal with the analysis of Lesya Ukrainka’s idiolect and epistolary, linguistic behavior stereotypes in letter communication, and Ukrainian authors’ fiction texts.
Keywords: linguostylistic analysis; ethnic stereotypes; epistolary texts; language behavior; epistolary communication